Professional English for Public Administration Students: Developing Workplace Communication Skills in Islamic Charity Institutions - Tira Nur Fitria; Afdaleni (Jurnal Ilmiah Ekonomi Islam, 2026)
This study explores how Professional English can be used to develop the workplace communication skills of Public Administration students in the context of Islamic charity institutions. This study employed a descriptive qualitative research design. Islamic charity institutions refer to organizations involved in the management and distribution of Islamic charitable funds and services, particularly Zakat, Infaq, and Sadaqah (ZIS). This study employed a descriptive qualitative research design. This study identifies eight workplace communication competencies relevant to Professional English for Public Administration students preparing for potential work in Zakat, Infaq, and Sadaqah (ZIS) institutions: providing ZIS service information, explaining administrative procedures, assisting donors and beneficiaries, handling inquiries and complaints, communicating with staff and stakeholders, managing administrative and service-related communication, developing professional English communication confidence, and developing ZIS-specific professional vocabulary. These competencies were developed through a synthesis of previous literature and consideration of ZIS administrative and service contexts rather than through direct questionnaires or interviews with ZIS employees, donors, or beneficiaries. The findings represent a researcher-developed conceptual framework that connects English learning with workplace communication functions. The competencies emphasize practical language use, including explaining services and procedures, giving instructions, assisting service users, responding to complaints, coordinating with colleagues and stakeholders, preparing administrative documents, and using specialized ZIS terminology. They integrate spoken and written communication, interpersonal skills, professional confidence, and context-specific vocabulary. The framework reflects ESP principles by shifting the focus from general English skills toward authentic occupational communication needs in ZIS administration and services. Examples of relevant situations include donor registration, zakat payment, beneficiary verification, assistance distribution, complaint handling, charity campaigns, stakeholder coordination, reporting, and administrative correspondence. Overall, the findings provide a conceptual foundation for developing contextualized Professional English materials and learning activities for Public Administration students, while future studies should validate these proposed competencies through empirical needs analysis involving ZIS administrators, amil, managers, students, graduates, donors, and beneficiaries.